Central Extensions and Nijenhuis Operators of Hom-δ-Jordan Lie Triple Systems - Qiang Li; Lili Ma (Advances in Mathematical Physics)
In this paper, the equivalence of central extensions and Hα,αV3T,V is proven in the study in Hom-δ-Jordan Lie triple systems. The concepts of Nijenhuis operators of Hom-δ-Jordan Lie triple systems are given. Moreover, a trivial deformation is got.